Could the Last Interglacial Constrain Projections of Future Antarctic Ice Mass Loss and Sea‐Level Rise?. Issue 10 (16th October 2020) - Gilford, Daniel M.; Ashe, Erica L.; DeConto, Robert M.; Kopp, Robert E.; Pollard, David; Rovere, Alessio
Abstract : Previous studies have interpreted Last Interglacial (LIG; ∼129–116 ka) sea‐level estimates in multiple different ways to calibrate projections of future Antarctic ice‐sheet (AIS) mass loss and associated sea‐level rise. This study systematically explores the extent to which LIG constraints could inform future Antarctic contributions to sea‐level rise. We develop a Gaussian process emulator of an ice‐sheet model to produce continuous probabilistic projections of Antarctic sea‐level contributions over the LIG and a future high‐emissions scenario. We use a Bayesian approach conditioning emulator projections on a set of LIG constraints to find associated likelihoods of model parameterizations. LIG estimates inform both the probability of past and future ice‐sheet instabilities and projections of future sea‐level rise through 2150. Although best‐available LIG estimates do not meaningfully constrain Antarctic mass loss projections or physical processes until 2060, they become increasingly informative over the next 130 years. Uncertainties of up to 50 cm remain in future projections even if LIG Antarctic mass loss is precisely known (±5 cm), indicating that there is a limit to how informative the LIG could be for ice‐sheet model future projections. The efficacy of LIG constraints on Antarctic mass loss also depends on assumptions about the Greenland ice sheet and LIG sea‐level chronology. However, improved field measurements and understanding of LIG sea levels still have potential to improve future sea‐level projections, highlighting the importance of continued observational efforts. Key Points: Improvements in Last Interglacial Antarctic mass loss estimates could appreciably reduce future sea‐level rise uncertainties Last Interglacial sea‐level constraints are increasingly informative with respect to Antarctic mass loss over 2060–2150 If Last Interglacial sea levels were known precisely, projected 2100 Antarctic mass loss could still have up to 50 cm uncertainties